RHETORIC STRATEGY IN CLASSROOM DISCUSSION - Eva Eri Dia; Suyono Suyono; Widodo Hs.; Sunaryo Sunaryo (RETORIKA: Jurnal Bahasa, Sastra, dan Pengajarannya, 2020)
This article aims to describe the pattern of question strategies and strategies for answering in class discussion activities. The documentation technique is used in collecting data sourced from verbal data, namely the speech of students who present the role as presenters and discussion participants, and lecturers who respond to the results of the discussion. The results of the analysis show that there is a pattern of rhetorical strategies generated in the speech of students in class discussion presentations. The pattern includes question strategies and answer strategies. In the question strategy in class discussion there are four formulas, among others; (1) description + question + marriage - is there in the speech of the audience and questioner ,(2) description + question + explanation is in the lecturer speech, (3) question + description is in the questioner's speech, (4) question + explanation + question is in the speech questioner. Whereas in the strategy of answering in class discussions there are two strategies found, among others; (1) the directanswerstrategy is found in the answering speech and (2) the indirectanswerstrategy is found in the answering speech.